مشكلة الفقر في المجتمع الأفغاني: دراسة شرعية = The problem of poverty in Afghan society: a shariah-based study - Hamidi, Jamaluddin; Mohammed Yaqub, Mohammed Abullais Shamsuddin (IIUM Press, 2024)
تعتبر أفغانستان من البلدان الإسلامية التي يُعاني سكانها من الفقر المدقِع والمزمن، على الرغم من توافر الموارد الطبيعية فيها من المعادن، والمياه، والأراضي الزراعية، والبشرية. يهدف البحث إلى دراسة الجوانب العقائدية لمشكلة الفقر في المجتمع الأفغاني من خلال تحديد العوامل التي ترتبط بالعقيدة الدينية، وتسبب الفقر والفاقة، وكذلك تحليل العلاقة بين تلك العوامل وبين تفاقم مشكلة الفقر في المجتمع الأفغاني وخاصة في العقدين الأخيرين، بالإضافة إلى بيان آثار الفقر وخطورته على انتشار العقائد الفاسدة والأفكار المنحرفة في أفغانستان، وذلك بالاستناد إلى القرآن الكريم والسنة النبوية. ويعتمد البحث على المنهج الاستقرائي والوصفي في تتبع نصوص الكتاب والسنة وتفسيرها، وكذلك تتبع مظاهر الانحرافات العقائدية في المجتمع الأفغاني، ثم المنهج التحليلي لمناقشة تلك المظاهر وعلاقتها بمشكلة الفقر في المجتمع. ومن أبرز النتائج التي خلص إليها البحث أن هناك علاقة وثيقة بين الأمن الفكري والعقدي والأمن الاقتصادي، وأن مشكلة الفقر في المجتمع الأفغاني لها جوانب عقائدية يجب أن تؤخذ بنظر الاعتبار عند وضع السياسة لعلاجها، وأن الانحرافات العقدية والإعراض عن منهج الله يسبب الفقر، وأن مشكلة الفقر قد ساهمت في انتشار العقائد الفاسدة والانحرافات الفكرية، مما أثر سلبيًا على الاستقرار في المجتمع الأفغاني، كما أن تسلط العلمانية وانتشارها في العقدين الأخيرين أدى إلى إهمال الحلول والوسائل الإسلامية لمعالجة الفقر في أفغانستان. ***** Afghanistan, despite its abundance of natural resources such as minerals, water, agricultural land, and human capital, is among the Islamic countries whose inhabitants suffer from severe and chronic poverty. This research aims to study the religious and ideological aspects of the poverty problem in Afghan society by identifying the factors related to religious beliefs and causing poverty and deprivation. As well as analysing the relationship between these factors and the exacerbation of the poverty problem in Afghan society, in addition to elucidating the effects of poverty and its danger on the spread of corrupt beliefs and deviant ideas in Afghanistan, based on the Holy Quran and the Sunnah. The research relies on the descriptive and inductive method to track and interpret the texts (nuṣūṣ) of the Quran and the Sunnah, as well as for tracing the manifestations of religious deviations in Afghan society, then the analytical approach for discussing these manifestations and their relationship to the poverty problem in the society. The key findings of the research are that there is a close relationship between intellectual and religious security and economic security, and the poverty problem in Afghan society has religious aspects that must be considered when making a policy to treat it, and the religious deviations and turning away from the path (manhaj) of Allah cause poverty. As well as the poverty problem has contributed to the spread of corrupt beliefs and intellectual deviations, which negatively affect the stability of Afghan society. Moreover, the influence of secularism and its spread in the recent two decades has led to the neglect of Islamic solutions and approaches to address the poverty problem in Afghanistan.